2016
DOI: 10.1093/ofid/ofw151
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D as Adjunctive Host-Directed Therapy in Tuberculosis: A Systematic Review

Abstract: Vitamin D plays an important role in innate defenses against intracellular pathogens. Seasonal vitamin D insufficiency (VDI) due to reduced sun exposure far from the equator increases tuberculosis risk. Eight randomized controlled trials examined vitamin D as adjunctive therapy during tuberculosis treatment. The studies varied substantially regarding patient genetic backgrounds, the extent of baseline VDI, the administered dose, the study endpoints, and the quality of the reported data. One carefully performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 28 publications
(36 reference statements)
2
26
0
Order By: Relevance
“…In addition, highdose vitamin D3 regimens safely correct vitamin D3 deficiency without improving the rate of sputum Mtb clearance [89]. Inconsistent results regarding vitamin D-based HDT-TB may be due to the basal levels of vitamin D in the patient population, VDR polymorphisms, and geographic and/or ethnic variation associated with TB susceptibility [78,97,98]. In addition, it is difficult to show the comparative effects of randomized clinical trials in which standard TB drugs are given together with the adjuvant drug (e.g., vitamin D) or placebo.…”
Section: Challenges Of Autophagy-adjunctive Therapeutics For Clinicalmentioning
confidence: 99%
“…In addition, highdose vitamin D3 regimens safely correct vitamin D3 deficiency without improving the rate of sputum Mtb clearance [89]. Inconsistent results regarding vitamin D-based HDT-TB may be due to the basal levels of vitamin D in the patient population, VDR polymorphisms, and geographic and/or ethnic variation associated with TB susceptibility [78,97,98]. In addition, it is difficult to show the comparative effects of randomized clinical trials in which standard TB drugs are given together with the adjuvant drug (e.g., vitamin D) or placebo.…”
Section: Challenges Of Autophagy-adjunctive Therapeutics For Clinicalmentioning
confidence: 99%
“…VitD 3 as adjunct therapy in TB treatment has been utilized in several clinical trials, and the primary clinical outcomes are not always in line with the expected protective effects. A recent systematic review by Wallis et al has discussed eight clinical studies where vitD 3 was used as adjunctive therapy in TB treatment [152]. Among these eight studies only two of them showed significant microbiologically positive effects of vitD 3 .…”
Section: Clinical Trials and Host Directed Therapymentioning
confidence: 99%
“…The authors acknowledge that it is difficult to compare the studies because they are different in relation to patients' genetic backgrounds, baseline vitD 3 , administered dose, dosing schedule, study endpoints, and the quality of the reported results [152]. Another recent randomized and placebo-controlled trial with a high dose of vitD 3 (four biweekly doses of 3.5 mg) during TB treatment has been conducted in Mongolia [153].…”
Section: Clinical Trials and Host Directed Therapymentioning
confidence: 99%
“…Vitamin D has also been tested in many clinical trials involving large patient cohorts although there still appears to be no decisive effect on the clinical outcome of TB in treated individuals (reviewed by Wallis and Zumla, 2016). However, further clinical trials are warranted due to a clinical benefit observed in some of the studies described in the review.…”
Section: Small-molecule and Soluble Hdts For Mdr-tbmentioning
confidence: 99%